Revisão e avaliação morfométrica da mirmecomorfia em Bucranium O.Pickard-Cambridge, 1881(aranae, thomisidae) - Pizzetti, Daniela dos Passos (2019)
The genus of Bucranium spiders is composed of 4 species distributed in the Neotropical region. Species present morphology of the cryptic body, with diagnostic characteristics restricted to the male and female copulatory characteristics. Due to this crypticism and the morphological similarity of the tegument of the carapace of the spiders with as tegument of the ants, individuals of this genus are often found associated with the anthill. Considering the genus as a Peckhamian mimic, putatively mimic of Cephalotes. To verify these morphological similarities between the organisms, an analysis of geometric morphometry of the Bucranium carapace and related groups (Aphantochilus and Cephalotes) was carried and the taxonomic revision of the genus. Thus, the dissertation was divided into two chapters. The first corresponds to the taxonomic revision of the genus and consisted in the analysis of the genitalia of more than 200 specimens of Bucranium, coming from several museums and universities. Both species were photographed and described based on the morphological characteristics of the integument and genitalia. Our results demonstrated 7 new species of Bucranium, the synonymy of B. pulchra to B. affinis, the reestablishment of B. nigritarse and B. spinigera was proposed an species inquirenda. The second chapter corresponds to the morphometric evaluation of myrmecomorphy in Bucranium and related groups. Five species of Bucranium, two species of Aphantochilus and three species of Cephalotes (Formicidae) were photographed in frontal view (Cephalotorax) and dorsal view (Prosoma). Subsequently, 14 landmarks were marked in Cephalotorax and 20 landmarks in the Prossoma through the tpsDIG 232 program and analyzed in SoftWare R. Our results suggest through the Analysis of Principal Components and Canonical Variation sexual dimorphism in the form of Bucranium individuals, discretizing the females into groups well-resolved taxonomies. The males presented clusters overlap, probably because they presented morphological characteristics considered more cryptic when compared to the females. The analyzes performed in Bucranium and related groups showed dissimilarity between the genders, demonstrating that the mimetism present in Bucranium does not involve morphological similarity.